Minimally Invasive Surgery at Paropakar Maternity and Women’s Hospital - Baral, Gehanath; Joshi, Rijuta (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The purpose of this study is to review the reintroduced minimally invasive surgical practice in the hospital after a couple of decades long gap. Methods: It is a two years (2015 to 2017) retrospective cross-sectional study carried out in Paropakar Maternity and Women’s Hospital. The patients with pre-operative diagnosis of benign condition underwent laparoscopic surgery; hysteroscopy was diagnostic and operative both. Data were collected by demographics, indication of surgery, nature of surgery, complications, hospital stay and histo-pathological reports. Data were entered in the SPSS and MS-excel. Results were presented as tables and graphs. Results: Sixty five and 39 women underwent laparoscopic surgery and hysteroscopy respectively. None of them had major complications and hospital stay was1-3 days in majority. The most common age group was 31-35 years. Preoperative diagnoses of them were adnexal tumor in 47 women, fibroid uterus in six, AUB in two, ectopic pregnancies in four, PCOD in two and one women each with primary sub-fertility and POP Q II with elongated cervix. Laparoscopic cystectomy was performed on 25 women for the adnexal masses while 13 women underwent laparoscopic oophorectomy for the ovarian masses. Total laparoscopic hysterectomy was the second commonest surgery (n=12). On histopathological examination of the ovarian tissues, mature cystic teratoma was the commonest finding (n=18) followed by the endometriotic cysts (n=9), benign serous cystadenoma (n=7) and mucinous cystadenoma (n=4). Conclusions: Laparoscopy and hysteroscopy procedures have become the alternative in surgical modality at this hospital.